Interaction between the autokinase EpsE and EpsL in the cytoplasmic membrane is required for extracellular secretion in Vibrio cholerae. - Sandkvist, M (1995)
Vibrio cholerae secretes a number of proteins important for virulence, including cholera toxin. This process requires the products of the eps genes which have homologues in genera such as Aeromonas, Klebsiella and Pseudomonas and are thought to form a membrane-associated multiprotein complex. Here we show that the putative nucleotide-binding protein EpsE is associated with and stabilized by the cytoplasmic membrane via interaction with EpsL. Analysis of fusion proteins between EpsE and the homologous ExeE from Aeromonas hydrophila demonstrates that the N-terminus of EpsE contains the EpsL binding domain and determines species specificity. An intact Walker A box, commonly found in ATP-binding proteins, is required for activity of EpsE in vivo and for autophosphorylation of purified EpsE in vitro. These results indicate that both the kinase activity of EpsE as well as its ability to interact with the putative cytoplasmic membrane protein EpsL are required for translocation of toxin across the outer membrane in Vibrio cholerae.